Combined XRF‐SEM analysis of varnished pottery: the case of Syracuse and Adrano (Sicily) archaelogical finds. (20th November 2012) - Aquilia, Erica; Barbera, Giovanni; Barone, Germana; Crupi, Vincenza; Longo, Francesca; Majolino, Domenico; Mazzoleni, Paolo; Venuti, Valentina
<x xml:space="preserve">Abstract</x> Micro‐destructive and non‐destructive X‐Ray fluorescence techniques and scanning electron microscopy coupled with energy‐dispersive spectrometry have been applied for the analysis of ten samples of Hellenistic black‐varnished pottery, coming from archaeological excavations in Syracuse and Adrano (South Italy, Sicily). Micro‐morphological and compositional investigations, together with statistical data processing, have shown several differences among the varnishes of the specimen found in the two sites. In particular, Syracuse varnishes are characterised by a more homogeneous composition and well‐defined raw materials, whereas Adrano samples show a higher variability, probably linked to the use of different raw materials and the poorer quality of the varnish as well. The obtained results attest that, as Syracuse black pottery is concerned, the production technique is at an advanced level, whereas Adrano manufacture seems to be less specialised. Copyright © 2012 John Wiley & Sons, Ltd.